Semiotic aspects of visual communication: from semantics to pragmatics - Kiklewicz, Aleksander (Papers in Linguistics, 2024)
Referring to the tradition of describing natural languages, the author considers semantic and pragmatic aspects of visual iconic signs. The most important characteristic of iconic signs are the lack of a second articulation (i.e. no division of the image into non-significant elements) as well as the lack of assigning a visual form to a specific mental representation. In the author’s view, an iconic sign shows what the recipient can think about in relation to what they know about something that is similar to what they see. The author distinguishes two types of inference: identifying and completive, showing how the interpretation of visual images is affected by the user’s semantic intention. The article presents two types of applications of counterfactual signs: manipulative and implicative.